Dominant suppressor genes of p53-induced apoptosis in Drosophila melanogaster - Szlanka, Tamás; Lukacsovich, Tamás; Bálint, Éva; Virágh, Erika; Szabó, Kornélia; Hajdu, Ildikó; Molnár, Enikő; Lin, Yu-Hsien; Zvara, Ágnes; Kelemen-Valkony, Ildikó; Méhi, Orsolya; Török, István; et al. (G3 (Bethesda, Md.), 2024)
One of the major functions of programmed cell death (apoptosis) is the removal of cells that suffered oncogenic mutations, thereby preventing cancerous transformation. By making use of a Double-Headed-EP (DEP) transposon, a P element derivative made in our laboratory, we made an insertional mutagenesis screen in Drosophila melanogaster to identify genes that, when overexpressed, suppress the p53-activated apoptosis. The DEP element has Gal4-activatable, outward-directed UAS promoters at both ends, which can be deleted separately in vivo. In the DEP insertion mutants, we used the GMR-Gal4 driver to induce transcription from both UAS promoters and tested the suppression effect on the apoptotic rough eye phenotype generated by an activated UAS-p53 transgene. By DEP insertions, 7 genes were identified, which suppressed the p53-induced apoptosis. In 4 mutants, the suppression effect resulted from single genes activated by 1 UAS promoter (Pka-R2, Rga, crol, and Spt5). In the other 3 (Orct2, Polr2M, and stg), deleting either UAS promoter eliminated the suppression effect. In qPCR experiments, we found that the genes in the vicinity of the DEP insertion also showed an elevated expression level. This suggested an additive effect of the nearby genes on suppressing apoptosis. In the eukaryotic genomes, there are coexpressed gene clusters. Three of the DEP insertion mutants are included, and 2 are in close vicinity of separate coexpressed gene clusters. This raises the possibility that the activity of some of the genes in these clusters may help the suppression of the apoptotic cell death.
Keywords: Drosophila melanogaster; Promoter Regions, Genetic; Genes, Dominant; Drosophila Proteins; nádorový supresorový protein p53; Phenotype; zvířata; inzerční mutageneze; apoptosis; apoptóza; proteiny Drosophily; fenotyp; p53; supresorové geny; DNA Transposable Elements; Drosophila; Mutagenesis, Insertional; activating insertional mutagenesis; Genes, Suppressor; suppression; Animals; promotorové oblasti (genetika); Apoptosis; transpozibilní elementy DNA; dominantní geny; Tumor Suppressor Protein p53